2016
DOI: 10.15376/biores.11.3.7686-7696
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Strength of Some Adhesives in Heat-Treated Hornbeam (Carpinus betulus L.) Wood Used for Interior and Exterior Decoration

Abstract: Heat-treated wood has an ever-expanding market for exterior and interior applications. The objective of this study was to determine the effect of a heat treatment on the bonding strength of hornbeam (Carpinus betulus L.) wood that was bonded with melamine formaldehyde (MF), polyurethane (PUR), and polyvinyl acetate (PVAc-D4) adhesives. Hornbeam lamellas were heat treated at 150 °C, 175 °C, 200 °C, and 225 °C for 3 h and then bonded. The bonding strength of the specimens was determined. In addition, the density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Similar results for bonding thermally modified wood are also presented in the papers (Uzun et al, 2016;Andromachi & Ekaterini, 2018;Taghiyari et al, 2020). The authors noted that the decrease in strength is affected by wetting ability, microcracks, density, surface of thermally modified wood, and the physical-chemical characteristics of the adhesive.…”
Section: Resultssupporting
confidence: 73%
“…Similar results for bonding thermally modified wood are also presented in the papers (Uzun et al, 2016;Andromachi & Ekaterini, 2018;Taghiyari et al, 2020). The authors noted that the decrease in strength is affected by wetting ability, microcracks, density, surface of thermally modified wood, and the physical-chemical characteristics of the adhesive.…”
Section: Resultssupporting
confidence: 73%
“…The adhesion strength of heat treated wood can be affected by various factors such as the pH of the wood and its equilibrium moisture value. Heat treatment causes a decrease in the pH and equilibrium humidity of the wood [24,25]. Changes in the pH value of the wood surface may delay or accelerate the curing of adhesives, depending on the type of adhesive used for Bonding [26].…”
Section: Resultsmentioning
confidence: 99%
“…He reports that low equilibrium humidity values significantly delay the resin bonding performance. A series of studies have shown that the shear strength of wood is negatively affected by heat treatment temperature and processing time [29,27,24,30,31]. The adhesion strength, wood rupture and elongation values of the test samples after A1, A4 and A5 holding conditions are shown in Tables 3, 4 and 5, respectively (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thermal modifi cation process also reduces the surface wettability and increases surface brittleness, which then negatively affects bond performance of wood (Chu et al, 2016;Šernek et al, 2008;Kariž and Šernek, 2012;Uzun et al, 2016). However, shear strength and delamination tests performed on native and thermally modifi ed Norway spruce and poplar glued with PUR and MUF adhesives were found to meet the requirements for glued laminated timber (Šernek et al, 2008).…”
Section: Materijali I Metodementioning
confidence: 99%